PENERAPAN PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) GUNA EFISIENSI BIAYA PRODUKSI (Studi Kasus Pada Feodal Coffee and Roastery Kediri) - Nila Dwi Indriani (ICMA Nasional, 2023)
The purpose of this study was to determine whether the inventory control of coffee raw materials with the Economic Order Quantity ( EOQ) method is more optimal than the method applied by the Feodal Coffee and Roastery. The research data was obtained from the Feodal Coffee and Roastery company data in 2021 and conducted direct interviews with the company owners. The data analysis technique is done by calculating and analyzing the number of orders, the number of purchasing frequencies, safety stock, reorder point, and total inventory cost. From the results of the research that has been done, it is found that the total cost of raw material inventory using the method applied by the company is Rp 3.120.456, after being calculated using the EOQ method, the total inventory cost is Rp 2.039.512. So it can be seen that the inventory control of coffee raw materials using the Economic Order Quantity (EOQ) method is more optimal than the method applied by the Feodal Coffee and Roastery.